The causes of abnormal uterine bleeding in women with chronic psychogenic stress - K. V. Fedosiuk; L. V. Pakharenko; K. V. Chaika; V. M. Zhurakivskyi; O. M. Lasytchuk; O. M. Kusa (Zaporožskij Medicinskij Žurnal)
Abnormal uterine bleeding (AUB) is a common pathology in women of reproductive age. Chronic psychogenic stress significantly impacts the parameters of the menstrual cycle and can result in its disorders and AUB.